Analysis of types of dermal papillae on fingertips in a group of students from Jan Kochanowski University in the Kielce region of Poland - Kuder, Tadeusz; Nowak, Paulina (Medical Studies/Studia Medyczne, 2016)
Introduction : The patterns of dermal papillae show a high inter-individual variability, and their geographic and ethnic variability is also observed. Dermatoglyphs, apart from their wide use in the identification of persons, establishing fatherhood, etc., are used as an instrument for the assessment of genetically conditioned diseases, such as: Down syndrome, brachydactyly, and Klinefelter syndrome. Aim of the research: To test the distribution of the patterns of dermal papillae among university adolescents from Jan Kochanowski University (JKU) in the Kielce Region in comparison to data from other researchers from other regions of Poland. Material and methods : The research material comprised fingerprints of randomly selected students from the Kielce Region (50 females and 50 males), aged 19–25 years, studying at JKU in Kielce. Results and conclusions: The conducted study showed that the distribution of the types of patterns was similar to other regional groups and the Polish population, with certain simultaneous specific features. Loop patterns running in the direction of the ulna more often occurred on the fingertip pads of the right hand, whereas radial loops were more frequently observed on the fingertip pads of the left hand. Whorl patterns were more often noted in male than in female students. Arch and loop patterns were more frequently observed in female than in male students. Individual types of patterns showed certain preferences with respect to some fingers (loops – III and V; whorls – II and IV).